Análisis de atención al cliente a la población indígena y negra en el centro de salud Latacunga - Saquinga Villafuerte, Lourdes Isabel (2015)
This research focuses on customer service guide’s development. It was heading for all the staff working at Latacunga Health Center in order to get a good environment to indigenous and black population. At the first phase, it focused staff performing on their duties in each of Health Center departments and the service provided to this population. For this reason, there is a necessity to contribute to human values guide. It gives a relevance to good work performance in each of its professionals into the primary body such as the customer regardless of the social class to which they belong. At the second phase, it carried out at the surveys of each of clerk’s working in the health center….